'Getting on with the job': A systematised literature review of secondary trauma and post-traumatic stress disorder (PTSD) in policing within the United Kingdom (UK). (March 2022) - Foley, Jim; Hassett, Alex; Williams, Emma
The aim of this review is to identify and critically examine existing research relating to secondary trauma and Post-Traumatic Stress Disorder (PTSD) within UK police officers. A systematised literature review was conducted which identified 20 studies in police officers from Scotland, England, Wales and Northern Ireland. These studies comprised of terrorist incidents, mass disasters, general policing duties and officers working in rape and child abuse investigations. Key themes emerged regarding understanding the impact of trauma, the influence of police culture and understanding coping mechanisms. It also found a number of methodological limitations within the studies which are likely to have impacted on the results. This review highlighted that trauma in UK policing is still not understood and there is a stigma associated with officers seeking help. Recognising the impact of trauma on police officers and how trauma has affected them is crucial to ensure an effective and compassionate workforce which delivers a better service to the public. It is hoped that this review will address gaps in existing knowledge within the literature, consider implications for practice, as well as recommendations to be taken forward in this crucial area of research.